COMPARISON OF CERVICAL LAMINOPLASTY TECHNIQUES IN BIOMODELS - de Araújo Júnior, Francisco Alves (2024)
Background: There are several types of laminoplasty reported in the literature, but there are few studies comparing which one expands the canal the most. One of the ways to evaluate this comparison is by applying the techniques in a three-dimensional anatomical model. Objective: Define which laminoplasty technique provides the greatest increase in spinal canal dimensions. Method: This is an experimental study, a type of clinical trial. Initially, a patient was identified and diagnosed with cervical spinal canal stenosis at multiple levels, of degenerative etiology resulting in myelopathy. Magnetic resonance imaging and computed tomography of the patient's cervical spine were imported to a software program to print the anatomical model. A total of twenty identical cervical spine biomodels were printed, equally distributed into four groups: control, Open-door (OD), French-door (FD), and Two-open-doors (TOD) laminoplasty. The biomodels of the experimental groups were submitted to the laminoplasty surgical procedure, from C3 to C6, according to each technique. All specimens of the study were submitted to tomography, and the cross-sectional area and anteroposterior diameter of the vertebral canal were measured. The data were submitted to statistical analyses (ANOVA analysis) and p-value results < 0.05 were considered as statistically significant. An equivalence or non-inferiority test was applied in the absence of a statistical difference between the groups. Results: All techniques increased the dimensions of the spinal canal. OD laminoplasty was superior to FD in the area evaluation (OD: 2.17cm2; FD: 1.92cm2) and there was no statistical difference in increased anteroposterior diameter (OD: 10.97mm; FD:10.42mm). TOD laminoplasty (area: 2.30 cm2; diameter: 11.94 mm) that was superior to FD in both variables. There was no statistical difference between OD and TOD laminoplasty, although the latter tended to further expand the vertebral canal, based on the equivalence tests. Conclusion: The open-door technique expands the cross-sectional area of the spinal canal more than French-door laminoplasty with no significant difference in diameter. Two-open-doors laminoplasty increases the dimensions of the spinal canal more than the French-door, and it tends to be superior to Open-door laminoplasty.